Development of national tourism in Uzbekistan in recent years - Zebiniso Bobonorova Faxriddin qizi (Genius Journals, 2022)
In this article, we can see that the development of domestic tourism in our country from year to year, including the development of various types of domestic tourism, including pilgrimage tourism, and the work of our President in this area, laws and regulations, and also the introduction of several decrees in the development area.
Keywords: Tourism; domestic tourism; pilgrimage tourism; laws and decrees